Innovative electrochemical detection of emerging pollutants using MXene and carbon nanofiber modified screen-printed electrodes - Wong, Ademar [UNESP]; Santos, Anderson M.; Feitosa, Maria H.A.; Moraes, Fernando C.; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2025)
Disposable screen-printed electrodes based on carbon ink modified with MXene, and carbon nanofibers were developed as a cost-effective and simple electroanalytical platform for the sensitive detection of acid red 1 (AR) and carbaryl (CAR) in environmental samples. The electrochemical properties of the analytes were examined by cyclic voltammetry in the potential range of 0–1.2 V and at a scan rate of 50 mV s−1 using 0.10 mol L−1 phosphate buffer solution (pH 7.0) as the supporting electrolyte. During the anodic potential scan, two oxidation peaks were found at the potentials of 0.55 V and 1.05 V. Under optimized square wave voltammetry (SWV) conditions, the screen-printed sensor was used to construct an analytical curve with linear concentration ranges of 6.2 × 10−7 to 7.2 × 10−6 mol L−1 for AR and 2.0 × 10−6 to 3.9 × 10−5 mol L−1 for CAR, while the limits of detection for AR and CAR were determined to be 1.2 × 10−7 and 5.2 × 10−7 mol L−1, respectively. The screen-printed sensor was found to be highly selective, sensitive, stable, reproducible, and repeatable, while also being cost-effective and unaffected by the effects of potential interferents. The proposed sensor was successfully applied for the analysis of environmental samples, where it recorded recovery rates close to 100 %.